Exploring Dynamic Nexus between Economic Growth, Environmental Degradation, and Public Health in Pakistan: A Moderated Mediation Approach - Firdous , Rehana; Chatrath, Sarvjeet Kaur; Jadoon, Atif Khan; Iqbal, Munawar; Batool, Syeda Azra; Ul Hasan, Zameer (International Journal of Energy Economics and Policy, 2023)
Since the start of this century, much attention has been given to economic growth and environmental changes and their effects on human beings. The present study has developed a comprehensive model to discuss the nexus between economic growth, environmental degradation, and public health. Furthermore, renewable energy consumption and public health spending are used as moderators to make the model more inclusive. The time series data from 1972 to 2020 has been used, and a regression path modeling tool SPPS-PROCESS Model 29, has been applied to carry out the results. The results showed a positive and significant effect of economic growth on environmental degradation, while renewable energy consumption reduces environmental degradation. Furthermore, environmental degradation is negatively affecting the health status in Pakistan. The results of the total effects showed that economic growth positively contributes to public health with a low coefficient. The indirect conditional impact of economic growth on human health through the mediating role of environmental degradation becomes positive from negative in the long run due to renewable energy and public spending on health. Based on the result, some policies are suggested in the last section of this study.